ADDRESS SYSTEMS AND POLITENESS STRATEGIES IN BATU BARA MALAY SOCIAL INTERACTION - Efrizah, Doni; Puspita, Clara; Ali, Nurbaiti (Universitas Islam Sumatera Utara, 2025)
Language is more than a communication tool; it embodies cultural identity, social hierarchy, and shared values. In the Batu Bara Malay community, address systems function as structured linguistic expressions of age, rank, kinship, and familiarity, with respect and politeness being integral to interpersonal interactions—especially in addressing elders or individuals of higher status. However, the advent of globalization and social media has introduced new modes of communication among the younger generation, creating tension between traditional norms and emerging language practices. This study investigates the address systems and politeness strategies in the Batu Bara Malay community, focusing on how these are used and transformed in social interaction. Employing a qualitative descriptive approach and linguistic ethnography, data were gathered through in-depth interviews, participant observation, and documentation involving native speakers across varying ages and social strata. The findings highlight the complex variety of address terms and politeness strategies that reflect deep-rooted cultural values and social order. Despite generational shifts, the community continues to uphold linguistic traditions as a means of preserving cultural identity and maintaining social cohesion.